Компьютерный метод варьируемой кусочно-полиномиальной аппроксимации функций и решений обыкновенных дифференциальных уравнений - Ромм, Я.Е.; Джанунц, Г.А. (Кибернетика и системный анализ, 2013)
Комп’ютерний метод кусково-поліноміальної апроксимації функцій і розв’язок задачі Коші для систем звичайних диференціальних рівнянь будується на базі полінома Ньютона. Апроксимуючий поліном на підінтервалі перетворюється в форму з числовими коефіцієнтами, варіюється степінь полінома і число підінтервалів. Показано рівномірне сходження методу зі швидкістю геометричної прогресії в умовах двократної неперервної диференційованості функції і правої частини системи. Наближений розв’язок системи безперервно і безперервно диференційовано характеризується малою похибкою зокрема при розв’язанні жорстких задач. The computer method of piecewise polynomial approximation of functions and of the Cauchy problem solution for ordinary differential equations based on the Newton polynomial is presented. The approximating polynomial on a subinterval is converted to the form with numerical coefficients, the degree of the polynomial and the number of subintervals varies. The uniform convergence of the method at the rate of geometric progression is shown under conditions of double continuous differentiability of the function and of the right-hand side of the system. The approximate solution of the system is continuous, continuously differentiable, and is characterized by low error rate, in particular, when solving stiff problems.